2004
DOI: 10.1016/j.jtcvs.2003.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic pretreatment improves the efficacy of cellular cardiomyoplasty performed with fetal cardiomyocyte implantation

Abstract: Pretreatment of an infarcted region of the heart with angiogenic mediators such as VEGF can enhance the efficacy of cellular cardiomyoplasty, presumably by creating a more favorable environment for the survival of transplanted cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 30 publications
(63 reference statements)
4
45
2
Order By: Relevance
“…Although alteration of the environment in the recipient infarct region into which the cells are grafted might improve the survival of implanted cells (20), increased cellular tolerance to ischemia may be more beneficial. The induction of angiogenesis in the infarct region before implantation of cells was associated with only a modest improvement in ventricular function (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although alteration of the environment in the recipient infarct region into which the cells are grafted might improve the survival of implanted cells (20), increased cellular tolerance to ischemia may be more beneficial. The induction of angiogenesis in the infarct region before implantation of cells was associated with only a modest improvement in ventricular function (21).…”
Section: Discussionmentioning
confidence: 99%
“…One approach to this challenge is a two-stage process, where pro-vascularization interventions are employed initially, followed by seeding of a myogenic population. In any case, vascularization is clearly required for long term graft survival, and several studies have found over-expression of vascular endothelial growth factor (VEGF) enhances grafted cell survival [74][75][76]. Interestingly, adenoviral over-expression of hypoxia inducible factor-1α (HIF-1α) [77] with grafted skeletal myoblasts increased graft cell number, blood vessel formation and cardiac function.…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%
“…Recipient ischemic tissue may be inadequate for donor cell retention in sufficient quantity to allow for the desired effect, because the survival of cells from any source implanted in the myocardium varies between 1% and 10%. 11 Also, nonspecific delivery of donor cells to other body sites constitutes an unwanted potential side effect. Cell-based angiogenesis may therefore benefit from tissue engineered strategies to better administer cells and optimize their specific homing.…”
mentioning
confidence: 99%